10 practical priorities to prevent and manage serious allergic reactions: GA2LEN ANACare and EFA Anaphylaxis Manifesto - Antonella Muraro; Debra de Silva; Marcia Podesta; Aikaterini Anagnostou; Victoria Cardona; Susanne Halken; Pete Smith; Luciana Kase Tanno; Paul Turner; Margitta Worm; Montserrat Alvaro‐Lozano; Stefania Arasi; et al. (Clinical and Translational Allergy)
Abstract This Anaphylaxis Manifesto calls on communities to prioritise 10 practical actions to improve the lives of people at risk of serious allergic reactions. The Global Allergy and Asthma European Network and the European Federation of Allergy and Airways Diseases Patients' Associations (EFA) compiled patient‐centric priorities. We used qualitative consensus methods, research evidence and feedback from over 200 patient groups, stakeholder organisations and healthcare professionals. We encourage healthcare, education and food organisations to collaborate with people at risk of serious allergic reactions to tackle safety, anxiety and financial burdens for individuals and societies. Key priorities for prevention include awareness‐raising campaigns for the public and professionals, school and workplace initiatives and mandatory precautionary allergen labels on food. Priorities for improving immediate and long‐term management include educating healthcare professionals, patients and schools about when and how to use adrenaline, funding two approved adrenaline devices for everyone at risk, and facilitating access to allergy specialists. Integrated care pathways should include clinical and non‐clinical management options such as individualised risk assessment and quality of life assessment, self‐management plans, dietetic and psychosocial support and peer support. Organisations around the world are committing to work together towards these priorities.